Campanian ware from Mesas do Castelinho (Portugal) - Alves, Catarina (Rei Cretariae Romanae Fautorum Acta, 2015)
This paper aims to present the data concerning Campanian ware from Mesas do Castelinho from the vast collection of archaeological material recovered over 23 excavation campaigns (1989–2012) directed by Carlos Fabião and Amílcar Guerra. The ensemble is one of the most significant in what is now Portuguese territory, at least of those already published , and raises several issues, such as the presence of rare or unique forms or makes, but perhaps most importantly, the observation of stratigraphic sequences which allow us to establish a connection with the Romanization of the settlement, its relations with the surrounding territory and its integration in trade routes connected to the Mediterranean.